Multi-Attribute Auctioning Resource in Grids: Model and Protocols - Lili Ding; Xiaoling Wang; Wanglin Kang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Auction models and protocols are found efficient in managing resources allocation, which are a key technology in grid computing system. In this paper, a new multi-attribute multi-round reverse auction is proposed, and related reverse auction based protocols are designed. The resource user’s satisfaction degree is introduced into the traditional grid resource allocation problem to help the grid resource broker make multi-attribute decisions with incomplete information. Numerical simulating experiments show that our model and protocols can satisfy the resource user’s quality demand on multiple attributes, and achieve high efficiency in user utility. The results also illustrate that the on-line multi-attribute algorithm in ONMRA protocol has better performance in an on-line setting for grid allocation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3347